Does Change in Perception Following Counseling Result in Improved Quitting Outcome Among Malaysian Smokers? - Yasin, Siti Munira; Masilamani, Retneswari; Moy, Foong Ming; Koh, David (SAGE Publications (UK and US), 2015)
Objective: The authors examined the effects that change in perception about the advantages and disadvantages of smoking and quitting had on quitting outcome among smokers enrolled in a program for smoking cessation. Methods: A total of 185 smokers from 2 public universities who were interested in quitting received smoking cessation counseling on understanding the risks and benefits of quitting (or smoking) in addition to a course of free nicotine replacement therapy (NRT). A decisional balance questionnaire (DBQ) was administered at baseline and at 2 months postcounseling to determine and assess changes in smoking perception. Results: After counseling, 72.3% of smokers had reduced their perceptions about the advantages of smoking, and 66.4% had increased perceptions of disadvantages of smoking. At the eighth week, 51 participants (27%) had quit. Smokers who had reduced perceptions of the advantages of smoking had significantly higher quit rates compared with those with no improvement in perception (82.6% vs 17.4%; odds ratio = 2.47; 95% confidence interval = 1.00-6.10). Conclusion: After counseling, smokers did change their perception of the advantages and disadvantages of smoking during the quitting process. These changes are associated with a higher likelihood of smoking cessation.